Regio- and Enantioselective Iridium-Catalyzed Amination of Racemic Branched Alkyl-Substituted Allylic Acetates with Primary and Secondary Aromatic and Heteroaromatic Amines - Kim, Seung Wook (J Am Chem Soc, 2018)
The air and water stable π-allyliridium C,O-benzoate modified by (S)-tol-BINAP, (S)-Ir-II, catalyzes highly regio- and enantioselective Tsuji-Trost type aminations of racemic branched alkyl-substituted allylic acetates using primary or secondary (hetero)aromatic amines. Specifically, in the presence of (S)-Ir-II (5 mol%) in DME solvent at 60-70 °C, α-methyl allyl acetate 1a (100 mol%) reacts with primary (hetero)aromatic amines 2a-2l (200 mol%) or secondary (hetero)aromatic amines 3a-3l (200 mol%) to form the branched products of allylic amination 4a-4l and 5a-5l, respectively, as single regioisomers in good to excellent yield with uniformly high levels of enantioselectivity. As illustrated by the conversion of heteroaromatic amine 3m to adducts 6a-6g, excellent levels of regio- and enantioselectivity are retained across diverse branched allylic acetates bearing normal alkyl or secondary alkyl substituents. For reactants 3n-3p, which incorporate both primary and secondary aryl amine moieties, regio- and enantioselective amination occurs with complete site-selectivity to furnish adducts 7a-7c. Mechanistic studies involving amination of the enantiomerically enriched deuterium labelled acetate 1h corroborate C-N bond formation via outer-sphere addition.